Collapsing Structures and Public Mismanagement - Seibel, Wolfgang (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"In what is certain to become an indispensable book on public failures, their origins, and consequences, Wolfgang Seibel builds piece-by-piece a unique contribution to the study of rare events and the search for resilience in public policy. This is a must-read for those who want to better understand such 'black swan' events and the search for resilience." - Andrew B. Whitford, Professor at the School of Public and International Affairs, University of Georgia, USA "A must read for practitioners and scholars, Wolfgang Seibel's latest book provides profound insight in the intersection of public administration mismanagement and the absence of responsible leadership. An exceptional contribution to the field." - Janine O'Flynn, Professor of Public Management, The Australia and New Zealand School of Government, Australia This open access book is about mismanagement of public agencies as a threat to life and limb. Collapsing bridges and buildings kill people and often leave many more injured. Such disasters do not happen out of the blue nor are they purely technical in nature since construction and maintenance are subject to safety regulation and enforcement by governmental agencies. The book analyses four relevant cases from Australia, New Zealand, the USA and Germany. Rather than stressing well-known pathologies of bureaucracy as a potential source of disaster, this book argues, learning for the sake of prevention should aim at neutralizing threats to integrity and strengthening a sense of responsibility among public officials. Wolfgang Seibel is Professor of Politics and Public Administration at the University of Konstanz, and an Adjunct Professor of Public Administration at the Hertie School in Berlin, Germany. His new book is an outcome of the research project "Black Swans in Public Administration: Rare Organizational Failure with Severe Consequences" funded by the German Research Foundation (DFG).